KEMAMPUAN INFORMASI LABA DAN ARUS KAS DALAM MEMPREDIKSI DIVIDEN DI BURSA EFEK INDONESIA - Wulandari, Made Dwi; Sukartha, I Made (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
This study aims to determine the better predictor between earnings and operating cash flows in predicting dividend entities listed in Indonesia Stock Exchange. In this study that fulfil criteria of purposive sampling is as much as 159 entities with 393 observations. The result using MAPE analysis shows that in absolute terms, earnings is better in predicting dividend compared to operating cash flows. Statistically, data test using independent sample t-test concluded that there were no differences in the ability between earnings and operating cash flows in predicting dividend.
Keywords: Operating Cash Flow, Dividend, Earning, MAPE